Automatic control valve using servo motor - Zul Fadli, Mohamad Tohid (2013)
This thesis is about developing a small scale control system to control the flow rate of water by using a servo control valve. Arduino board as the microcontroller was used to make a control plant much easier. The simplify C/C++ programming language also is use to make control system coding. A servo motor with known characteristic in controlling the position with high accuracy and timing has been chosen to implement as a control valve in order to reduce error. This project originally is the flume project.A control valve controls the flow and velocity of water to maintain laminar flow before entering the flume. By accurate valve opening using servo motor and interface of Arduino programming language It is possible to develop a better control system in a large scale project on the future. The theory have been proved as the larger valve opening results in larger flow rate value. Based on the result, these small scale control flow system are capable to gradually reduce cost especially in control valve. The result also shows that using Arduino microcontroller a friendly-users control system efficiently.